MENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE PROBLEM POSING DALAM SETTING COOPERATIVE LEARNING PADA PEMBELAJARAN FISIKA DI KELAS X 2 SMA NEGERI 10 BANJARMASIN - Intan Rias Rindang Sari; Zainuddin Zainuddin; Abdul Salam M (Jurnal Ilmiah Pendidikan Fisika, 2017)
Students less active for learning because the learning just centered on the teacher so resulted in the low the results of learning and student activities. So the result done to improve student learning outcomes and activities with method of problem posing in setting the model of cooperative learning to electricity dynamic materials. This research was an action research such us: planning, acting, observing, reflection. The techniques of collected data used test, observations, and documentation. Data were analyzed by descriptive quantitative and qualitative. The result showed: (1) the implementation of lesson plan the first cycle is 97,36% and second cycle is 99,08% (2) student activities include be a good listener, want to ask, contribute ideas, and willing to work in the first and second cycle in well criteria, (3) learning outcomes of student in cycle I and II respectively , 66,66% ( not completed), 83,33% (completed). Obtained summary that method of problem posing in setting cooperative learning can improve student learning outcomes and activities.